Forecasting Tunisia's Future: A Lesson Learned from the Past - Januari Pratama Nurratri Trisnaningtyas (ijd-demos, 2022)
AbstractTunisia has become a success story of the peaceful revolution that presented modern dictatorship regime change, which inspired the Arab World. However, post regime transition caused plenty of political, security, and economic instability. Over the last decade, considerable domestic political unrest, combined with deep structural inequalities and increased public perceptions of government corruption, has come dangerously close to derailing its path toward democratic consolidation and stability. On July 25, 2021, President Kaïs Saïed undemocratically dismissed the prime minister and froze the parliament. He subsequently declared his right to rule by decree and his intention to amend the constitution and electoral law. Tunisia is once again thrown into a political crisis due to the event. This study examines similar factors contributing to Tunisia's 2010 and 2021 political problems based on single-country comparative studies and predicts Tunisia's political situation in the future. The study found that the political crises are laid on three key factors: economic problems, political Legitimacy, and the role of Youth. Subsequently, the author argues that Tunisia needs a clear political plan to achieve a stable democracy, particularly by addressing the economic issues as a priority and increasing public trust by eradicating chronic government corruption. Otherwise, the country is likely to return to the autocratic regime.Keywords: Comparative study, Democracy, Political crises, Post-Arab Spring, Tunisia. AbstrakTunisia telah menjadi kisah sukses revolusi damai yang menghadirkan perubahan rezim kediktatoran modern, yang menginspirasi Dunia Arab. Namun, transisi pasca rezim menyebabkan banyak ketidakstabilan politik, keamanan, dan ekonomi. Selama dekade terakhir, kerusuhan politik dalam negeri yang cukup besar, dikombinasikan dengan ketidaksetaraan struktural yang mendalam dan peningkatan persepsi publik tentang korupsi pemerintah, telah nyaris menggelincirkan jalannya menuju konsolidasi dan stabilitas demokrasi. Pada 25 Juli 2021, Presiden Kaïs Saïed secara tidak demokratis memberhentikan perdana menteri dan membekukan parlemen. Dia kemudian menyatakan haknya untuk memerintah melalui dekrit dan niatnya untuk mengubah konstitusi dan undang-undang pemilu. Tunisia sekali lagi dilemparkan ke dalam krisis politik karena peristiwa tersebut. Studi ini mengkaji faktor-faktor serupa yang berkontribusi terhadap masalah politik Tunisia 2010 dan 2021 berdasarkan studi komparatif satu negara dan memprediksi situasi politik Tunisia di masa depan. Studi ini menemukan bahwa krisis politik terletak pada tiga faktor utama: masalah ekonomi, legitimasi politik, dan peran Pemuda. Selanjutnya, penulis berpendapat bahwa Tunisia membutuhkan rencana politik yang jelas untuk mencapai demokrasi yang stabil, terutama dengan menangani masalah ekonomi sebagai prioritas dan meningkatkan kepercayaan publik dengan memberantas korupsi pemerintah yang kronis. Jika tidak, negara kemungkinan akan kembali ke rezim otokratis.Kata kunci: Studi perbandingan, Demokrasi, Krisis politik, Pasca Musim Semi Arab, Tunisia